2013
DOI: 10.1002/2013jc008891
|View full text |Cite
|
Sign up to set email alerts
|

On the heterogeneity of stratified-shear turbulence: Observations from a near-field river plume

Abstract: [1] The heterogeneity of turbulent structure in a near-field river plume is evaluated through the application of three distinct measurement techniques: turbulent overturn analysis, direct turbulence measurement using microstructure sensors mounted on an autonomous underwater vehicle (AUV), and a larger scale control volume approach. These techniques exploit the preturbulent potential energy available for conversion to turbulent energy, the kinetic energy associated with active turbulence, and the artifacts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Though the ratio can vary as a Kelvin‐Helmholtz billow ages (Smyth, ) and observational estimates include large uncertainties (Ferron et al, ; Mater et al, ), the ratio has been supported by numerous open‐ocean (Wesson & Gregg, ) and lake (Dillon, ) measurements. In estuaries and plumes, which better reflect the conditions observed in this study, the ratio has also been observed to hold (Peters, ; Orton, ), with comparisons between other methods yielding values within the same order of magnitude (MacDonald & Horner‐Devine, ; MacDonald et al, ). A comparison of these overturn scales in the Deep Cove plume, however, shows that the expected linear relationship did not hold here (Figure ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Though the ratio can vary as a Kelvin‐Helmholtz billow ages (Smyth, ) and observational estimates include large uncertainties (Ferron et al, ; Mater et al, ), the ratio has been supported by numerous open‐ocean (Wesson & Gregg, ) and lake (Dillon, ) measurements. In estuaries and plumes, which better reflect the conditions observed in this study, the ratio has also been observed to hold (Peters, ; Orton, ), with comparisons between other methods yielding values within the same order of magnitude (MacDonald & Horner‐Devine, ; MacDonald et al, ). A comparison of these overturn scales in the Deep Cove plume, however, shows that the expected linear relationship did not hold here (Figure ).…”
Section: Discussionsupporting
confidence: 80%
“…A comparison of methods to derive TKE dissipation rates from VMP profiles where (a) unsorted temperature (dashed) and buoyancy frequency squared ( N 2 ) profile (solid), (b) the instantaneous Thorpe scale ( L T ), and (c) direct microstructure‐derived ϵ (solid) and Thorpe scale‐derived ϵ T (dotted). The shaded region around each profile represents one standard deviation from the distribution mean, calculated using the method described in MacDonald et al (). The mean is calculated from nine VMP profiles taken approximately 1 km from the tailrace discharge site, downstream of DCA.…”
Section: Resultsmentioning
confidence: 99%
“…Especially in geophysical scenarios, this is a common scenario, with examples including river plumes (e.g. MacDonald, Carlson & Goodman 2013), the deepening of the upper-ocean wind-mixed layer (e.g. Pollard, Rhines & Thompson 1972) and the very intricate case of cloud-top entrainment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this limitation should be addressed in future studies by conducting intensive field surveys to investigate the inertial and K‐H instability processes generated around tidal plumes. A combination of “tow‐yo” (e.g., MacDonald et al, ) CTD/ADCP casts, and low‐altitude remote sensing, such as the balloon photography used this study, could be a powerful tool for evaluating the Rayleigh criterion (equation ) and Richardson number (equation ) in an actual situation. However, we will still encounter the difficulty arising from the fact that the spatiotemporal scales of these processes are 1 order of magnitude smaller than the field observations obtained in the coastal waters.…”
Section: Discussionmentioning
confidence: 99%